Estimation of Energy Potential and Power Generation from Tidal Basin in Coastal Area of Malaysia - Nazani, Nazri; Shahrani, Anuar; F., Basrawi; Ahmmad Shukrie, Md Yudin; Siti, Aishah (EDP Sciences, 2016)
This paper presents the potential of tidal energy in Malaysia. Malaysia is heavily depending on the fossil fuel to satisfy the energy demand. However, this reserve energy is reported will be depleted. The population growth also caused the demand on energy increase over the year. This situation can lead to the global warming and climate change that be a major concern around the world. As an alternative, renewable energy become a solution in order to reduce the usage of conventional energy such as fossil fuel, coal and gas. One of the renewable energy that can be used is from ocean energy. Since the tidal energy is not study thoroughly in Malaysia and Malaysia has a potential sites that can implement this tidal energy for electricity generation to meet the local demand. This tidal energy can be harnessed in several approach such as by using tidal barrage single basin with single mode generation consist ebb-mode and flood-mode of generation and the other approach of single mode is double-mode of generation. In order to meet the local demand, single-mode generation and double-mode generation was studied by getting the number of population at that area, the electricity demand then from that data the basin area is estimated for power generation. The result shows that double-mode generation is one of the approaches that meet the local demand for electricity